2006
DOI: 10.1051/0004-6361:20065034
|View full text |Cite
|
Sign up to set email alerts
|

Catalog extraction in SZ cluster surveys: a matched filter approach

Abstract: We present a method based on matched multifrequency filters for extracting cluster catalogs from Sunyaev-Zel'dovich (SZ) surveys. We evaluate its performance in terms of completeness, contamination rate and photometric recovery for three representative types of SZ survey: a high resolution single frequency radio survey (AMI), a high resolution ground-based multiband survey (SPT), and the Planck all-sky survey. These surveys are not purely flux limited, and they loose completeness significantly before their poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
318
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 244 publications
(329 citation statements)
references
References 51 publications
9
318
2
Order By: Relevance
“…Some 1625 massive clusters out to z = 1 are expected over the whole sky. We assume the selection function by Melin et al (2006), shown in middle panel of Fig We show in Fig. 31 the angular number densities per redshift bin.…”
Section: All-sky Surveysmentioning
confidence: 99%
“…Some 1625 massive clusters out to z = 1 are expected over the whole sky. We assume the selection function by Melin et al (2006), shown in middle panel of Fig We show in Fig. 31 the angular number densities per redshift bin.…”
Section: All-sky Surveysmentioning
confidence: 99%
“…Below, we recall the main features of the multifrequency matched filters. More details can be found in Herranz et al (2002) or Melin et al (2006).…”
Section: Multifrequency Matched Filtersmentioning
confidence: 99%
“…We build a multifrequency matched filter (Herranz et al 2002;Melin et al 2006) based on the known spectral shape of the thermal SZ effect and the shape of the universal pressure profile of Arnaud et al (2010). This profile was derived from REXCESS (Böhringer et al 2007), a sample expressly designed to measure the structural and scaling properties of the local X-ray cluster population by means of an unbiased, representative sampling in luminosity.…”
Section: Introductionmentioning
confidence: 99%
“…We extracted the SZ signal using multi-frequency matched filters (MMF, Herranz et al 2002;Melin et al 2006), which optimally filter and combine maps to estimate the SZ signal. As input, the MMF requires information on the instrumental beam, the SZ frequency spectrum, and a cluster profile; noise autoand cross-spectra are estimated directly from the data.…”
mentioning
confidence: 99%